The relevance of inter-personal and inter-organizational ties for interaction quality and outcomes of research collaborations in South Korea - Martin Hemmert (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2015)
Informal social ties have long been recognized as relevant not only for interaction between individuals, but also for knowledge transfer and other important outcomes of business activities. This applies in particular to East Asian countries such as South Korea where informal networks are widely believed to be prevalent in economy and society. However, less is known about their role in inter-organizational collaboration efforts, such as research collaborations. This research examines the relevance of inter-personal and inter-organizational ties for interaction quality and outcomes of research collaborations in South Korea. Two types of research collaborations are studied: new product development (NPD) collaborations between companies and university-industry research collaborations (UICs). Inter-personal ties are found in a majority of both types of collaborations being studied. However, whereas inter-organizational tie strength is strongly related to interaction quality and outcomes of research partnerships, inter-personal ties are not. Implications for research and for the management of inter-organizational research collaborations are shown.
Keywords: 330; social ties; research collaborations; interaction quality; knowledge acquisition; Korea